Critical role of ARID3B in the expression of pro-apoptotic p53-target genes and apoptosis - Pratama, Endrawan; Tian, Xiaohui; Lestari, Widya; Iseki, Sachiko; Arief Ichwan, Solachuddin Jauhari; Ikeda, Masa-Aki (Elsevier, 2015)
ARID3A and ARID3B are transcriptional targets of p53. Recently, it has been reported that ARID3A plays a critical role in the transcriptional activation of pro-arrest p21 in response to DNA damage. However, the role of ARID3B in the p53 regulatory pathway remains poorly understood. Here we show that ARID3A and ARID3B specifically bind to putative ARID3-binding sites in p53 target genes in vitro and in vivo. ARID3B and, to a lesser extent, ARID3A silencing blocked transcriptional activation of pro-apoptotic p53 target genes, such as PUMA, PIG3, and p53. Furthermore, ectopic ARID3B, to a lesser extent, ARID3A expression activated the pro-apoptotic gene expression, and only ARID3B induced apoptosis. Finally, ARID3B but not ARID3A silencing blocked apoptosis induction following DNA damage. These results indicated that, although ARID3B and ARID3A share overlapping functions, ARID3B play a key role in the expression of pro-apoptotic p53-target genes and apoptosis.